Pharmacist Led Intervention on Inhalation Technique among Asthmatic Patients for Improving Quality of Life in a Private Hospital of Nepal - Anita Yadav; Parbati Thapa (Pulmonary Medicine, 2019)
Purpose. Asthma is a chronic disease which cannot be cured but can be controlled. Although drug therapy is used to relieve and prevent symptoms of asthma and treat exacerbations, still a good asthma control and a better quality of life in many patients is suboptimal due to improper use of inhalation technique. Thus, this interventional study was conducted to evaluate the effect of a pharmacist intervention on asthma control, quality of life and inhaler technique in adult asthmatic patients. Patients and Methods. A total of 72 patients who met the inclusion criteria and agreed to give written consent were enrolled in the study. These patients were randomly divided into two groups i.e., test group (36) and control group (36) by simple block randomization technique. Test group were the interventional groups. Mini Asthma Quality of Life Questionnaire (AQLQ), Asthma Control Questionnaire (ACQ) and structured questionnaires were used to sort the information like quality of life, asthma control and demographic details. They were counselled by the pharmacist about the asthma management and proper use of inhalers. Out of 72 patients, only forty six patients came for follow up after one month. Data were entered and analyzed using Statistical Package for Social Sciences (SPSS) software version 20. Results. A significant change was observed in the mean score of quality of life (p=0.001) in test group as well as control group, however change in the mean score of asthma control in the test group (p=0.001) was more significant as compared to the control group (p=0.099). Inhalation technique was found to be improved significantly after intervention among patients using the metered dose inhaler and dry powder inhaler. Majority of the patients were prescribed with Methylxanthines (24.5%) followed by combined Beta 2 agonists and Inhaled Corticosteroids (21.7%). Conclusion. Pharmacist provided intervention improves the quality of life, asthma control and inhalation technique among asthmatic patients.